Crafting Political Institutions in Africa. Electoral Systems and Systems of Government in Rwanda and Zambia Compared - Alexander Stroh (German Institute of Global and Area Studies (GIGA), 2007)
Scholars of institutional design attribute large importance to the choice of new institutions. The comparative analysis of how Rwanda and Zambia crafted their new electoral systems and the systems of government regards procedural, structural and rational choice variables which may influence the option for particular solutions. External influences and the type of transition are determinants that can decide which actors make their interests prevail. The degree of innovation or conservatism of new institutions is mainly a result of the speed of the process and the kind of actors involved. However, rational reflections on how to produce legitimacy and minimize personal risks which take into consideration the state of conflict in the country decide on the speed and on innovative outcomes. The structured analysis of only two cases uncovers already that it is rather difficult to realise the transfer of design recommendations into reality. – – Die große Zahl an Veröffentlichungen zum Thema 'institutional design' zeigt, welche Bedeutung die Politikwissenschaft der Wahl neuer politischer Institutionen beimisst. Diese vergleichende Untersuchung der Institutionengestaltung in Ruanda und Sambia berücksichtigt historisch-prozessuale, strukturelle und interessenorientierte Variablen, die auf die Entscheidung für bestimmte Wahl- und Regierungssysteme Einfluss ausüben können. Es zeigt sich, dass externe Faktoren und der Verlaufstyp der Transition entscheidend darauf einwirken können, welche Akteure in der Lage sind, ihre Interessen durchzusetzen. Die Prozessgeschwindigkeit und die Struktur der beteiligten Akteure sind maßgebend dafür, wie innovativ oder konservativ die neuen Institutionen gestaltet werden. Das Interesse an Legitimität und persönlicher Risikominimierung bestimmen wiederum die Prozessgeschwindigkeit und die Gestaltung innovativer Institutionen. Diese rationalen Entscheidungen berücksichtigen dabei die Konfliktsituation im Lande. Der strukturierte Vergleich zweier Fälle legt nahe, dass der Transfer von Empfehlungen des institutional design als schwierig gelten muss.
Keywords: 300; institutions; institutional design; transition; electoral system; Rwanda; Zambia